The Effectiveness of The Implementation of The Farmer Card Program in Distributing Subsidized Fertilizers in Tasikmadu District, Karanganyar Regency - Monika Ardela; Suminah Suminah; Eksa Rusdiyana (Westscience Press, 2024)
In order to actualize distribution and control that are right on target, one of the government programs that is employed as a tool to redeem subsidized fertilizers is called the Farmer Card. Among the objectives of this study are the following: 1) To describe and analyze the variables of non-formal education, land ownership, farming experience, and social environment, as well as the effectiveness of the implementation of the Farmer Card Program in distributing subsidized fertilizers; 2) To analyze the influence of factors that affect the effectiveness of the program on the effectiveness of the implementation of the Farmer Card Program in Tasikmadu District. The research is conducted using a quantitative approach, and the venue was chosen on purpose to be in the Tasikmadu District community. When using the proportional simple random sampling approach, there were a total of seventy individuals that participated in the survey. The IBM SPSS Statistics 25 application was utilized for the analysis of the data, and a multiple linear regression test was performed. The findings of the research indicate that the following elements are included in the high category: (1) the factors that pertain to non-formal education are included in the high category; (2) the domain of land ownership is included in the very limited category; (3) the farming experience is included in the old category; and (4) the social environment is included in the high category. The effectiveness of the implementation Farmer Card Program in distributing subsidized fertilizers in Tasikmadu District is included in the category of quite good in terms of the success of the target, the success of the program and satisfaction with the program; (2) Non-formal education, the extent of land ownership and the social environment have a significant effect on the effectiveness of the implementation of the Farmer Card Program, while farming experience has no significant effect.